2010
DOI: 10.1155/2011/290489
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Inhibits Inflammation Reaction by Upregulating Vasoactive Intestinal Peptide in Rats with Adjuvant‐Induced Arthritis

Abstract: Acupuncture is emerging as an alternative therapy for rheumatoid arthritis (RA). However, the molecular mechanism underlying this beneficial effect of acupuncture has not been fully understood. Here, we demonstrated that electroacupuncture at acupoints Zusanli (ST36), Xuanzhong (GB39); and Shenshu (BL23) markedly decreased the paw swelling and the histologic scores of inflammation in the synovial tissue, and reduced the body weight loss in an adjuvant-induced arthritis rat model. However, the electrical stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 44 publications
1
39
0
Order By: Relevance
“…ing pain [29] , rheumatoid arthritis [18] , carrageenan-induced inflammatory pain [23] , and ALS [3] . However, the mechanism underlying the effects of acupuncture remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ing pain [29] , rheumatoid arthritis [18] , carrageenan-induced inflammatory pain [23] , and ALS [3] . However, the mechanism underlying the effects of acupuncture remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the effectiveness of acupuncture in treating inflammatory diseases (i.e. rheumatoid arthritis) [18] and neurodegenerative diseases including Alzheimer's disease [19] , Parkinson's disease [20] and ALS [3] . However, the molecular mechanisms underlying the effectiveness of acupuncture remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Acupuncture also appears to affect the immune system and therefore can have a direct effect on inflammation [18, 19], including reducing neutrophil invasion during sepsis [20]. The role of inflammation in carcinogenesis has been extensively investigated and well documented [2123].…”
Section: Introductionmentioning
confidence: 99%
“…Continuous-wave stimulation was selected at a frequency of 5 Hz and intensity of 2 mA (6805-AII, Shantou Medical Equipment Factory Co., Ltd.) [2729]. An individual EA session was administered daily for 20 min for 7 days, with 2-day rest for the course of treatment, for 4 consecutive weeks.…”
Section: Methodsmentioning
confidence: 99%